Validation of the Portuguese version of the Clinical Impairment Assessment (CIA) in eating disorders' patients - Vaz, Ana Rita Rendeiro Ribeiro (2020)
Purpose: The purpose of the study was to assess the psychometric properties of the Portuguese version of the Clinical Impairment Assessment (CIA) in eating disorders (ED) patients. Method The CIA is a 16-item brief self-reported instrument developed to assess psychosocial impairment secondary to EDs. The CIA was administered to a clinical sample of 237 women with EDs and a college sample of 196 women. The clinical sample completed the Eating Disorders Examination Questionnaire, the Beck Depression Inventory and the Outcome-45 Questionnaire. Reliability, confirmatory factor analysis, validity, and clinically significant change were calculated. Results Confirmatory factor analysis validated the original 3-factor structure showing an adequate model fit. CIA showed good psychometric properties with high internal consistency, good convergent validity with the EDE-Q, the OQ-45, and the BDI. For divergent validity, participants CIA scores in the clinical sample were significantly higher than in the non-clinical sample. ROC curve analysis provided a cutoff of 15. For known-groups validity participants' scoring above CIA cutoff reported significantly higher CIA scores. In addition, non-underweight participants and participants reporting the presence of dysfunctional ED behaviors had significantly higher CIA scores. Finally, for clinically significant change, a reliable change index of 5 points was obtained to consider a reliable change in the CIA global score. Conclusions Our findings support the validity and clinical utility of the CIA as a good self-report measure to be used in both clinical and research settings.